MEDICAL-AND-SOCIAL CHARACTERISTICS OF TEENAGERS AND YOUNG MEN BOTH BELOW THE CONSCRIPTION AGE AND DUE FOR CONSCRIPTION IN THE KRASNODAR TERRITORY - S. N. LINCHENKO; I. A. ZHMAKIN; S. V. POROYSKIY; A. V. ARUTYUNOV; V. M. BONDINA; V. I. HMELIK (Кубанский научный медицинский вестник, 2017)
Medical-and-social characteristics as well as their connection with the health status of teenagers and young men below the conscription age and those due to conscription in the Krasnodar territory have been studied. The low level of their medical competence and prophylactic activity has been established. It was found necessary to plan priority guidelines for the improvement of medical support of these categories of the population as well as to create continuous system of hygienic education for social and age groups of young people.